Improving the mechanisms for developing the speed capabilities of young sprint swimmers - Ponimasov, O.E. (Theory and Practice of Physical Culture, 2026)
Abstract Objective of the study is to investigate the influence of alactic, glycolytic and aerobic energy production mechanisms on the performance of young swimmers in short-distance swimming. Methods and structure of the study. In a test involving a stepwise increase in load, average and maximum power outputs were measured at a rotation speed of 70 rpm for arm-driven exercise and 60 rpm for leg-driven exercise. Correlation coefficients were calculated between swimming speed and anaerobic and aerobic capacity. Results and conclusions. It has been established that the activating stimuli of speed-strength exercises, designed to develop maximum power in the arms and legs, lead to a deepening of the adaptive changes in swimmers’ bodies.